A PERCEPTION ON MILK PRODUCTION MANAGEMENT IN GOLDEN GLORY OF CITY - BERNARDO, LUCIANA VIRGINIA MARIO; FARINHA, MAYCON JORGE ULISSES SARAIVA; SILVA, ALEX FERREIRA DA; RUVIARO, CLANDIO FAVARINI (Revista Ciências Sociais em Perspectiva, 2016)
<pre style="text-align: justify; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial">This article aims to analyze the impact of management, cooperation and public policies applied to the dairy sector in the glory of Dourados, Mato Grosso do Sul Milk production has the function of generating income to farmers and to feed the local economic system, which also includes the fix small producers in the field. So put it, for the study and the construction of the article was prepared a questionnaire intended to collect data that would enable discussion and analysis of results. As the theoretical basis, it discusses the importance of the dairy supply chain for the performance of South Mato Grosso state agribusiness, the need for public policies for the qualification and production management, and the need for qualification of the workforce of small producers. Furthermore, the text addresses the cooperative's contribution to the competitive maintenance of small producers in the face of market competition requirements.